Disruption of a conserved region of Xist exon 1 impairs Xist RNA localisation and X-linked gene silencing during random and imprinted X chromosome inactivation. - Senner, C; Nesterova, T; Norton, S; Dewchand, H; Godwin, J; Mak, W; Brockdorff, N (2011)
In XX female mammals a single X chromosome is inactivated early in embryonic development, a process that is required to equalise X-linked gene dosage relative to XY males. X inactivation is regulated by a cis-acting master switch, the Xist locus, the product of which is a large non-coding RNA that coats the chromosome from which it is transcribed, triggering recruitment of chromatin modifying factors that establish and maintain gene silencing chromosome wide. Chromosome coating and Xist RNA-mediated silencing remain poorly understood, both at the level of RNA sequence determinants and interacting factors. Here, we describe analysis of a novel targeted mutation, Xist(INV), designed to test the function of a conserved region located in exon 1 of Xist RNA during X inactivation in mouse. We show that Xist(INV) is a strong hypomorphic allele that is appropriately regulated but compromised in its ability to silence X-linked loci in cis. Inheritance of Xist(INV) on the paternal X chromosome results in embryonic lethality due to failure of imprinted X inactivation in extra-embryonic lineages. Female embryos inheriting Xist(INV) on the maternal X chromosome undergo extreme secondary non-random X inactivation, eliminating the majority of cells that express the Xist(INV) allele. Analysis of cells that express Xist(INV) RNA demonstrates reduced association of the mutant RNA to the X chromosome, suggesting that conserved sequences in the inverted region are important for Xist RNA localisation.